Gel-state polymer electrolyte battery and preparation method thereof
By coating polymer monomer layers on the positive electrode, negative electrode and separator surface of the lithium battery, the problems of easy leakage of electrolyte and uneven distribution of polymers in the lithium battery are solved, forming a uniform gel electrolyte layer, which improves the heat of the battery Stability and safety performance.
Patent Information
- Application Number
- CN202411325008.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-13
AI Technical Summary
The organic liquid electrolyte used in existing lithium batteries is easy to leak, flammable and explosive, and the uneven distribution of polymer monomers in the battery leads to an increase in the viscosity of the gel polymer electrolyte, hindering the infiltration of the electrolyte and the battery. safety performance.
By uniformly coating the polymer monomer layer on the positive electrode, negative electrode and separator surface of the battery, and reacting with the initiator in the electrolyte to form a gel polymer electrolyte, ensuring that the electrolyte is completely wrapped and solidified to form a uniform gel Electrolyte layer.
It improves the thermal stability and safety performance of gel-state batteries, reduces battery impedance, and ensures the integrity and electrochemical performance of lithium ion channels.
Smart Images

Figure CN119133623A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new energy, and in particular relates to a gel polymer electrolyte and a preparation method thereof. Background Art
[0002] The lithium battery industry has developed rapidly in recent years, especially in the fields of 3C digital and electric vehicles. However, as the energy density of batteries continues to increase, safety issues have gradually become a concern for consumers, and the industry has also listed this issue as a top priority. At present, most common lithium batteries use organic liquid electrolytes, and organic liquid electrolytes are difficult to avoid leakage and flammability and explosion. This problem can be solved by using polymer monomers for in-situ curing to prepare gel electrolyte semi-solid batteries, wrapping the electrolyte in the polymer, making the polymer conduct lithium ions, and making the electrolyte lose fluidity, thereby reducing the leakage problem and safety risks of the battery. The in-situ curing technology currently used is to directly add polymer monomers and initiators to the electrolyte at the same time, and the electrolyte penetrates and infiltrates the pole piece and the diaphragm together, and then through heating, ultraviolet irradiation or battery pulse curing, the monomers are polymerized under the action of the initiator to form polymers, and the electrolyte is wrapped and fixed to form a gel polymer that conducts lithium ions but does not flow.
[0003] The prior art has the following defects: (1) Since monomers are added to the electrolyte, the viscosity of the electrolyte will be higher than that of the electrolyte of the liquid battery, which will seriously affect the wetting ability of the electrolyte in the battery pole piece; (2) Since the monomers are added to the electrolyte and then injected into the battery, the uniformity of their distribution on the surface of the pole piece / diaphragm is affected by the overall wetting ability of the electrolyte; (3) The monomers are limited by their compatibility with the electrolyte solvent, so that the infiltration speed of the monomers in the pole piece / diaphragm is often slower than that of the electrolyte solvent, and stratification occurs on the pole piece (separation of the monomers and the solvent); (4) During the battery infiltration (activation) process at room temperature, the in-situ polymerization reaction begins to occur slowly. Even if the speed is not as fast as under high temperature conditions, it is sufficient to rapidly increase the viscosity of the electrolyte, significantly hindering the infiltration of the electrolyte in the pole piece / diaphragm.
[0004] The above defects make it difficult for the monomers and the gel polymers they generate to be evenly distributed on the surface of the electrode / diaphragm. There is no gel polymer electrolyte in some areas, while the polymer concentration in the gel in other areas is too high, and some electrolytes that are not wrapped by the polymer exist in the battery in liquid form. The remaining liquid electrolyte cannot effectively solve the fluidity of the electrolyte, and the unevenly distributed gel polymer cannot effectively isolate the positive and negative electrodes, so it cannot effectively improve the thermal stability and safety performance of the battery. Since the local concentration of the polymer in the gel is too high, it will lead to an increase in battery impedance. The lack of gel polymer electrolyte in some areas will lead to the loss of lithium ion channels and the interface between the active material and the electrolyte, resulting in the loss of SEI / CEI membranes, failure of negative electrode lithium insertion and an increase in battery impedance, which ultimately reduces the electrochemical performance of the battery. Summary of the invention
[0005] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions: One of the purposes of the present invention is to provide a method for preparing a gel polymer electrolyte battery, the preparation method comprising: Assembling a battery cell structure with at least a positive electrode, a negative electrode and a separator, wherein a polymer monomer is uniformly distributed on at least a partial surface of at least one of the positive electrode, the negative electrode and the separator; An electrolyte is injected into the battery core structure, and the electrolyte is fully contacted with the polymer monomer, so that the polymer monomer contacts the initiator in the electrolyte and undergoes a polymerization reaction to generate a gel polymer electrolyte, thereby obtaining a gel polymer electrolyte battery.
[0006] In some embodiments, the preparation method specifically includes: providing a solution containing polymer monomers; Applying the solution containing the polymer monomer on the positive electrode, the negative electrode and the surface of the separator of the battery, and removing at least part of the solvent in the solution, so as to form a polymer monomer layer on the surface of the positive electrode, the negative electrode and the separator; The positive electrode, negative electrode and separator containing the polymer monomer layer are assembled into a battery core structure, and an electrolyte containing an initiator is injected into the battery core structure to react to form a gel polymer electrolyte, which is then activated, in-situ cured, formed and aged in sequence to form a gel polymer electrolyte battery.
[0007] The method provided by the present invention allows polymer monomers to be evenly distributed on the surface of the positive electrode, the negative electrode, and the diaphragm, so that when the positive electrode, the negative electrode, and the diaphragm contact the electrolyte, the polymer monomers thereon can react with the initiator in the electrolyte to form a uniformly distributed polymer electrolyte. This preparation method can completely cover the surface of the above-mentioned electrode structure with a gel polymer electrolyte, and the polymer content in the gel at different parts of the battery remains uniform, so that the liquid electrolyte is fully wrapped by the polymer and solidified into a gel; it solves the problem in the prior art that due to the uneven distribution of monomers and the polymer electrolyte finally formed, some areas have no polymer electrolyte, the polymer content and concentration in the gel in some areas are too high, and some electrolytes cannot be wrapped by the polymer and exist in liquid form. At the same time, the preparation method of the present invention is simple and easy to implement, does not require major changes to the existing polymer semi-solid battery production process, and is easy to industrialize.
[0008] In some embodiments, coating the solution containing the polymer monomer on the positive electrode, negative electrode and diaphragm surface of the battery specifically includes: making the polymer monomer layer cover at least two surfaces of the diaphragm opposite to the positive electrode and the negative electrode, and covering the rest of the positive electrode and the negative electrode except the tab welding position.
[0009] In some embodiments, the positive electrode includes a positive electrode active material, and the polymer monomer layer covers the positive electrode active material on the positive electrode; the negative electrode includes a negative electrode active material, and the polymer monomer layer covers the negative electrode active material on the negative electrode. Thus, the active materials of the positive electrode and the negative electrode can be evenly and completely covered by the polymer electrolyte membrane layer.
[0010] In some prior art, polymer monomers are mixed in positive and negative electrode slurries and homogenized together. These solutions are because the monomers are fixedly embedded between the positive / negative electrode active particles after homogenization and have no fluidity, and cannot fully contact with the electrolyte on the interface of the active material, and the monomers cannot contact each other, which leads to difficulties in the formation of gel polymers (including chain initiation and chain growth difficulties); secondly, if the polymer monomers are directly added to the negative electrode slurry, since the negative electrode is generally aqueous and has low compatibility with oily organic monomers, it will cause great difficulties in the dispersion of the homogenate, which is easy to cause slurry sedimentation, and only adding it to the positive electrode slurry will not produce a uniform gel polymer electrolyte between the negative electrode and the separator; and, since the polymer is an electronic insulator, if it is uniformly present between the active materials, it will inevitably lead to a decrease in conductivity, and some active materials will be isolated and inactivated, greatly reducing the battery capacity. The solution of the present invention can make the polymer electrolyte film layer uniformly and completely cover the electrode active material, and the formed complete gel polymer electrolyte coating layer can effectively isolate the contact between the positive and negative electrode plates and the active material from the outside. For example, when the battery generates heat / is heated and the diaphragm shrinks, it can effectively prevent the battery from short-circuiting and further releasing heat; after the battery is punctured, it can effectively prevent the positive and negative active materials from contacting with oxygen in the air, which can play a flame retardant role, thereby significantly improving the thermal stability and safety performance of the battery. In addition, the complete and fitting coating of the positive and negative active materials by the gel electrolyte can make the interface between the active material and the electrolyte more complete, avoiding the inability to extract / insert lithium due to the lack of ion channels, thereby causing lithium precipitation / non-insertion of lithium, and further improving the electrochemical performance and safety performance of the battery.
[0011] In some embodiments, the mass concentration of the polymer monomer in the solution is 0.1% to 10wt%. Different polymer monomer solution concentrations help achieve different polymer monomer coating surface densities; when a higher coating surface density is desired, the concentration of the polymer monomer solution used can be increased accordingly to improve the coating efficiency; when a lower coating surface density is desired, the concentration of the polymer monomer solution used can be reduced accordingly to help improve the uniformity of the coating. However, the monomer solution concentration will not have a direct impact on the absolute value of the final monomer coating surface density.
[0012] In some embodiments, the coating amount of the solution containing the polymer monomer on the surface of the positive electrode sheet, the negative electrode sheet and the separator is such that the coating surface density of the polymer monomer is 0.5-10 g / m 2. The "coating surface density" mentioned in the present invention refers to the density of the polymer monomers alone after removing the solvent of the polymer monomer solution. If the coating surface density is too low, the polymer monomers will not be able to completely and fully cover the surface of the electrode active material and the diaphragm, which will cause difficulties in chain growth during the polymer formation process, and the electrolyte will not be completely wrapped, and ultimately it will not be possible to form a completely solidified gel electrolyte, affecting the improvement of safety performance; if the coating surface density is too high, it will lead to excessive monomer content on the surface of the electrode active material and the diaphragm, and the formed polymer will be too dense, which will reduce the lithium ion conductivity and increase the interface impedance, thereby reducing the electrical performance.
[0013] In some embodiments, the method used to apply the solution containing the polymer monomer on the positive electrode, negative electrode and separator surface of the battery includes one or more of spraying, scraping, roller coating, or slit coating. In some preferred embodiments, the method used is spraying, because spraying can achieve better uniformity of the polymer monomer layer under low coating conditions.
[0014] In some embodiments, the preparation method specifically includes: heat treating the positive electrode, the negative electrode and the separator containing the solution to remove at least part of the solvent in the solution; the temperature of the heat treatment is T b溶剂 -50℃ <T<T b单体 -50℃, T b溶剂 is the boiling point of the solvent used in the solution, T b单体 is the boiling point of the polymer monomer.
[0015] In some embodiments, the heat treatment time is 5 min to 30 min.
[0016] In some embodiments, the solvent used in the solution includes a polar solvent having a solubility of more than 5 wt % in the polymer monomer and a boiling point lower than the boiling point of the polymer monomer.
[0017] In some embodiments, the solvent includes one or a combination of water, an alkane solvent, an alcohol solvent, and an ether solvent, but is not limited thereto.
[0018] In some embodiments, the solvent includes one or a combination of water, N-methylpyrrolidone, ethanol, ethylene glycol, isopropanol, and ether, but is not limited thereto.
[0019] The polymer monomer used in the present invention may be any one or a combination of monomers used to form gel polymer electrolytes in the prior art, such as monomers having epoxy bonds, double bonds, etc. that can undergo polymerization reactions, and the present invention does not impose any particular limitation on this.
[0020] In some embodiments, the mass concentration of the initiator in the electrolyte is 0.1-3wt%.
[0021] The initiator in the electrolyte can be any one or a combination of initiators that promote monomer polymerization, such as free radical initiators, cationic initiators, etc., which can be specifically selected according to the type of polymer monomer, and the present invention does not impose any particular limitation on this. The solvent of the electrolyte can be selected according to the type of battery actually prepared, and can be any one or a combination of solvents commonly used in the prior art, such as ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, dipropyl carbonate, etc.
[0022] In some embodiments, the activation is carried out at room temperature for 1 to 5 days, preferably 2 to 3 days.
[0023] In some embodiments, the in-situ curing method includes heating, ultraviolet irradiation, battery pulse, etc., the curing temperature is 30~70°C, preferably 45~60°C, and the curing time is 1~48h.
[0024] In some embodiments, after the battery is aged, a capacity division step is also included.
[0025] The above-mentioned positive electrode sheet, negative electrode sheet, and diaphragm can be the positive electrode, negative electrode, and diaphragm materials commonly used in existing gel polymer electrolyte batteries, and the electrode active material used can be any active material in the prior art, and the present invention does not make special restrictions on this. For example, the positive electrode sheet includes but is not limited to ternary, lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, sodium positive electrode materials, etc., the negative electrode sheet includes but is not limited to artificial graphite, hard carbon, natural graphite, mesophase microspheres, silicon oxide compounds, silicon-carbon composite materials, silicon, silicon alloys, etc., and the diaphragm includes but is not limited to polymer diaphragms, ceramic diaphragms, nanoporous diaphragms, composite diaphragms, etc.
[0026] A second object of the present invention is to provide a gel polymer electrolyte battery, wherein the gel polymer electrolyte battery is prepared according to the method described in any one of the above technical solutions.
[0027] Compared with the prior art, the present invention has at least the following beneficial effects: (1) The preparation method of the gel polymer electrolyte battery provided by the present invention can improve the distribution uniformity and coating integrity of the gel polymer on the surface of the electrode and the diaphragm, improve the thermal stability and safety performance of the battery, reduce the battery impedance and thus improve the battery electrical performance; (2) The preparation method provided by the present invention forms a complete polymer electrolyte layer on the surface of the positive electrode sheet, the negative electrode sheet and the separator of the battery. When the electrolyte is injected into the battery cell, the liquid electrolyte can be completely wrapped by the uniform polymer, thereby avoiding the residual flowable liquid electrolyte, thereby reducing safety risks and significantly improving the thermal stability and safety performance of the gel battery; (3) The preparation method of the present invention can also maintain uniform polymer content in the gel of different structural parts of the battery, thereby making the impedance of different parts of the battery more uniform, avoiding the problem of lithium ion channel obstruction or absence caused by excessive polymer content in a certain area, lack of polymer coating in a certain area, and the increase of local / overall impedance resulting in negative electrode lithium plating / non-lithium embedding, thereby further improving the electrochemical performance and safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 , Figure 2 is a SEM image of the negative electrode surface at different magnifications in Example 1 of the present invention; Figure 3 , Figure 4 is a SEM image of the negative electrode surface at different magnifications in Comparative Example 3 of the present invention; Figure 5 This is a diagram of the disassembly interface of the negative electrode of the battery prepared in Example 1 of the present invention when fully charged; Figure 6 This is a diagram of the fully charged disassembly interface of the positive electrode of the battery prepared in Example 1 of the present invention; Figure 7 This is a diagram of the disassembly interface of the negative electrode of the battery prepared in Comparative Example 3 of the present invention when fully charged; Figure 8 This is a diagram of the fully charged disassembly interface of the positive electrode of the battery prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.
[0031] Unless otherwise specified, the raw materials and reagents used in the specific embodiments of the present invention are all commercially available.
[0032] Example 1 This embodiment provides a gel polymer electrolyte battery and a preparation method thereof, which specifically comprises the following steps: Pour 10 g of butyl methacrylate and 90 g of ethanol into a beaker and stir with a magnetic stirrer at 500 rpm for 10 min to form a uniform butyl methacrylate solution; Prepare the positive electrode sheet with the formula of lithium iron phosphate (Yuneng YN-5): PVDF (US Solvay 5130): CNT (Jiangsu Tiannai LB107-44) = 96:2:2, wet homogenization, transfer double-sided continuous coating, surface density 320g / m 2 , compaction density 2.4g / cc, aluminum foil 16um; preparation of negative electrode, the formula is graphite (Bai Te Rui AGP-2L-D): CMC (Japan Daishiro 2200): SP (Cabot): SBR (Daoying GD1346L) = 95.5:1.3:1.2:2, wet slurry, transfer double-sided continuous coating, surface density 140g / m2, compaction density 1.55g / cc, copper foil 12um; The prepared butyl methacrylate solution was sprayed on the lithium iron phosphate positive electrode sheet, the graphite negative electrode sheet except the outer surface of the pole ear welding position and the double-side surface of the diaphragm (PE base film 9+Al2O3 ceramic coating 3um) respectively, and the coating surface density was 2g / m 2 , and heat treatment at 60°C for 10 min; The positive electrode sheet, negative electrode sheet and separator coated with butyl methacrylate are assembled into a 554065 wound soft-pack battery (the separator ceramic layer faces the positive electrode, the positive electrode sheet is 610 mm long and 57 mm wide, and the number of winding layers is 17; the negative electrode sheet is 680 mm long and 58.5 mm wide, and the number of winding layers is 18; the outermost negative electrode wraps the positive electrode, and the separator wraps the negative electrode, and the designed capacity is 1438 mAh); 4.6 g of electrolyte (PLB18602, 1 wt% of initiator BPO) was injected into the assembled battery, and then the battery was pre-sealed, activated at room temperature for 48 h, in-situ cured at 45 °C for 12 h, and subjected to formation (0.02C charged to 10% SOC, 0.05C charged to 20% SOC, 0.1C charged to 50% SOC, 0.2C charged to 80% SOC) and capacity division (0.2C / 1C capacity division) to finally obtain a gel polymer electrolyte battery.
[0033] The battery was tested on the Xinwei battery testing system to evaluate its electrochemical performance: voltage window 2.0-3.65V, 3C discharge capacity retention rate is 91.4% of 0.2C, 3C charge capacity retention rate is 88.5% of 0.2C; after 1C room temperature cycle for 1000 weeks, the capacity retention rate is 95.5%; -10℃ discharge capacity retention rate is 33.5% of that at room temperature, 60℃ discharge capacity retention rate is 105.7% of that at room temperature; at room temperature and 50% SOC, 2C charge and discharge for 10s, discharge DCR is 57.5mΩ, and charge DCR is 57.3mΩ.
[0034] The pass rate of the needle puncture test (iron needle diameter 3mm) is 95%, the pass rate of the hot box test (heating at 170℃ for 1h) is 95%, the pass rate of the overcharge test (0.5C overcharge to 5V, cut-off current is 0.2mA) is 85%, and the pass rate of the over-discharge test (0.5C over-discharge to 0V) is 90%.
[0035] Embodiments 2 to 8 The difference between Examples 2 to 8 and Example 1 is that the relevant process parameters are changed as shown in Table 1, and the rest are implemented in the same way as Example 1.
[0036] Comparative Example 1~2 The difference between Comparative Examples 1 and 2 and Example 1 is that the relevant process parameters are changed as shown in Table 1, and the rest are implemented in the same manner as Example 1.
[0037] Table 1 Relevant process parameters of Examples 1-8 of the present invention
[0038] Comparative Example 3 Comparative Example 3 provides a method for preparing a gel polymer electrolyte battery, which specifically comprises the following steps: Prepare the positive electrode sheet with the formula of lithium iron phosphate (Yuneng YN-5): PVDF (US Solvay 5130): CNT (Jiangsu Tiannai LB107-44) = 96:2:2, wet homogenization, transfer double-sided continuous coating, surface density 320g / m 2 , compaction density 2.4g / cc, aluminum foil 16um; preparation of negative electrode, the formula is graphite (Bai Te Rui AGP-2L-D): CMC (Japan Daishiro 2200): SP (Cabot): SBR (Daoying GD1346L) = 95.5:1.3:1.2:2, wet slurry, transfer double-sided continuous coating, surface density 140g / m2, compaction density 1.55g / cc, copper foil 12um; The positive electrode sheet, negative electrode sheet and separator are assembled into a 554065 wound soft-pack battery (the separator ceramic layer faces the positive electrode, the positive electrode sheet is 610 mm long and 57 mm wide, and the number of winding layers is 17; the negative electrode sheet is 680 mm long and 58.5 mm wide, and the number of winding layers is 18; the outermost negative electrode wraps the positive electrode, and the separator wraps the negative electrode, and the design capacity is 1438 mAh); An electrolyte containing butyl methacrylate (PLB18602, initiator BPO added in an amount of 1 wt %) was prepared, wherein the content of butyl methacrylate in the electrolyte was 12%, and 4.6 g of the electrolyte containing butyl methacrylate was injected into the assembled battery (so that the butyl methacrylate content of the battery of Comparative Example 3 was equivalent to that in Example 1), and then the battery was pre-sealed, activated at room temperature for 48 h, in-situ cured at 45°C for 12 h, and subjected to formation (0.02C charged to 20% SOC, 0.05C charged to 25% SOC, 0.1C charged to 50% SOC, 0.2C charged to 80% SOC) and capacity division (0.2C / 1C capacity division) to obtain a gel polymer electrolyte battery.
[0039] The prepared gel polymer electrolyte battery was tested by the same method as in Example 1. The test results are shown in Table 2.
[0040] Figure 1 , Figure 2 The following are SEM images of the negative electrode surface prepared in Example 1 at different magnifications. Figure 3 , 4 The following are SEM images of the negative electrode surface of Comparative Example 3 at different magnifications. Figure 1 , Figure 2 It can be seen that the polymer electrolyte membrane layer uniformly and completely covers the negative electrode active material, and the particle outline of the active material is observed from the electron microscope image. Figure 3 , Figure 4 The polymer electrolyte membrane layer in the negative electrode cannot completely cover the surface of the negative electrode active material, and the edges of the main material particles can still be clearly seen. Figure 4 It can be clearly seen that the polymer distribution is uneven, with some areas having a large thickness and being able to completely cover the surface, and some areas with exposed negative electrode particles.
[0041] Figure 5 This is a disassembled interface diagram of the negative electrode of the battery prepared in Example 1. It can be seen that the polymer electrolyte membrane layer is evenly distributed on the surface of the electrode, without obvious patchy or regional differences. Figure 7 This is the interface diagram of the negative electrode of the battery prepared in Example 3 when it is fully charged. The polymer electrolyte membrane layer is unevenly distributed in patches. The membrane layer is more obvious in the areas where the electrolyte infiltrates earlier at the upper and lower ends, and less obvious in the area in the middle where the electrolyte infiltrates later.
[0042] Figure 6This is a disassembled interface diagram of the positive electrode of the battery prepared in Example 1. It can be seen that the polymer electrolyte membrane layer is relatively evenly distributed on the surface of the electrode, without obvious patchy and regional differences, and the degree of adhesion to the diaphragm is relatively light. Figure 8 This is the interface diagram of the fully charged positive electrode of the battery prepared in Example 3. It can be seen that the polymer electrolyte membrane layer (darker in color) is unevenly distributed in patches. The membrane layer is more obvious in the areas at the upper and lower ends where the electrolyte infiltrates earlier, and the membrane layer is less obvious in the middle area where the electrolyte infiltrates later. The white triangles at the upper and lower ends are due to the thicker membrane layer, which causes the ceramic coating on the bonding diaphragm.
[0043] Comparative Example 4 Prepare an electrolyte containing butyl methacrylate (PLB18602, the amount of initiator BPO added is 1wt%), wherein the content of butyl methacrylate in the electrolyte is 12%; spray the above electrolyte on the surface of the diaphragm (PE base film 9+Al2O3 ceramic coating 3um) until the corresponding surface density of butyl methacrylate is 4g / m 2 (the butyl methacrylate content of the battery in comparative example 4 is made equivalent to that in example 1); after the spraying is completed, it is cured in situ at 45° C. for 12 hours to polymerize into a gel polymer electrolyte; Prepare the positive electrode sheet with the formula of lithium iron phosphate (Yuneng YN-5): PVDF (US Solvay 5130): CNT (Jiangsu Tiannai LB107-44) = 96:2:2, wet homogenization, transfer double-sided continuous coating, surface density 320g / m 2 , compaction density 2.4g / cc, aluminum foil 16um; preparation of negative electrode, the formula is graphite (Bai Te Rui AGP-2L-D): CMC (Japan Daishiro 2200): SP (Cabot): SBR (Daoying GD1346L) = 95.5:1.3:1.2:2, wet slurry, transfer double-sided continuous coating, surface density 140g / m 2 , compacted density 1.55g / cc, copper foil 12um; The above-mentioned positive electrode sheet, negative electrode sheet and separator are assembled into a 554065 wound soft-pack battery (the separator ceramic layer faces the positive electrode, the positive electrode sheet is 610mm long and 57mm wide, and the number of winding layers is 17; the negative electrode sheet is 680mm long and 58.5mm wide, and the number of winding layers is 18; the outermost negative electrode wraps the positive electrode, and the separator wraps the negative electrode, and the designed capacity is 1438mAh); then the battery is pre-sealed, activated at room temperature for 48h, and subjected to formation (0.02C charged to 10% SOC, 0.05C charged to 20% SOC, 0.1C charged to 50% SOC, 0.2C charged to 80% SOC), capacity division (0.2C / 1C capacity division), and finally a gel polymer electrolyte battery is obtained.
[0044] Only the electrolyte containing monomers is coated on the surface of the diaphragm to form a gel polymer. Although the gel polymer can be evenly distributed on the diaphragm, after being assembled into a battery, the gel polymer cannot fit perfectly on the surface of the positive / negative active material to form a tight coating layer, which easily causes gaps that cannot conduct lithium ions between the active material and the gel electrolyte formed on the surface of the diaphragm, causing difficulties in lithium insertion and extraction and forming defective areas; for the negative electrode, the area with gaps cannot insert lithium because lithium ions cannot smoothly reach the surface of the active material, and the nearby area is prone to lithium precipitation due to excessive excess lithium ions, which affects the battery performance.
[0045] The present invention tests the relevant performance of the batteries obtained in the above embodiments and comparative examples, and the test results are shown in Table 2: Table 2 Relevant performances of batteries obtained from the examples of the present invention and comparative examples ;
[0046] In addition, the present invention also verifies the performance of the gel polymer electrolyte battery formed when the concentration of the solution containing the polymer monomer is 0.1wt%, 2wt%, and 5wt%, and the effect is equivalent to that of Example 1. The present invention also adopts the above method to coat different polymer monomers on the surface of different types of positive electrode materials, negative electrode materials and separators, and the performance of the prepared gel polymer electrolyte battery is improved compared with the battery prepared by the method of the prior art.
[0047] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0048] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0049] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another element.
Claims
1. A method for preparing a gel polymer electrolyte battery, characterized in that: include: Assembling a battery cell structure with at least a positive electrode, a negative electrode and a separator, wherein a polymer monomer is uniformly distributed on at least a partial surface of at least one of the positive electrode, the negative electrode and the separator; An electrolyte is injected into the battery core structure, and the electrolyte is fully contacted with the polymer monomer, so that the polymer monomer contacts the initiator in the electrolyte and undergoes a polymerization reaction to generate a gel polymer electrolyte, thereby obtaining a gel polymer electrolyte battery.
2. The preparation method according to claim 1, characterized in that: Specifically include: providing a solution containing polymer monomers; Applying the solution containing the polymer monomer on the positive electrode, the negative electrode and the surface of the separator of the battery, and removing at least part of the solvent in the solution, so as to form a polymer monomer layer on the surface of the positive electrode, the negative electrode and the separator; The positive electrode, negative electrode and separator containing the polymer monomer layer are assembled into a battery core structure, and an electrolyte containing an initiator is injected into the battery core structure to react to form a gel polymer electrolyte, which is then activated, in-situ cured, formed and aged in sequence to form a gel polymer electrolyte battery.
3. The preparation method according to claim 2, characterized in that: Specifically include: The polymer monomer layer covers at least two surfaces of the separator opposite to the positive electrode and the negative electrode, and covers the remaining parts of the positive electrode and the negative electrode except the electrode ear welding position; And / or, the positive electrode includes a positive electrode active material, and the polymer monomer layer covers the positive electrode active material on the positive electrode; the negative electrode includes a negative electrode active material, and the polymer monomer layer covers the negative electrode active material on the negative electrode; And / or, the mass concentration of the polymer monomer in the solution is 0.1% to 10wt%; And / or, the coating amount of the solution containing the polymer monomer on the surface of the positive electrode sheet, the negative electrode sheet and the separator is such that the coating surface density of the polymer monomer is 0.5-10 g / m 2 .
4. The preparation method according to claim 2, characterized in that: The method of coating the solution containing the polymer monomer on the surface of the positive electrode, the negative electrode and the separator of the battery includes one or more of spraying, scraping, roller coating or slit coating, preferably spraying.
5. The preparation method according to claim 2, characterized in that: Specifically include: The positive electrode, the negative electrode and the separator containing the solution are heat-treated to remove at least part of the solvent in the solution; the temperature of the heat treatment is T b溶剂 -50℃ <T<T b单体 -50℃, T b溶剂 is the boiling point of the solvent used in the solution, T b单体 is the boiling point of the polymer monomer.
6. The preparation method according to claim 5, characterized in that: The heat treatment time is 5 min to 30 min.
7. The preparation method according to claim 2, characterized in that: The solvent used in the solution includes a polar solvent having a solubility of more than 5wt% in the polymer monomer and a boiling point lower than the boiling point of the polymer monomer; preferably, the polar solvent includes one or more combinations of water, alkane solvents, alcohol solvents, and ether solvents; more preferably, the solvent includes one or more combinations of water, N-methylpyrrolidone, ethanol, ethylene glycol, isopropanol, and ether.
8. The preparation method according to claim 1 or 2, characterized in that: The mass concentration of the initiator in the electrolyte is 0.1-3wt%.
9. The preparation method according to claim 2, characterized in that: The activation is carried out at room temperature for 1 to 5 days; and / or the in-situ curing is carried out at a temperature of 30 to 70° C. for 1 to 48 hours.
10. A gel polymer electrolyte battery, characterized in that: The method is prepared by the method described in any one of claims 1 to 9.
Citation Information
Cited By
Whole-domain integrated gel semi-solid battery and preparation method thereof
CN120473574A
